2012
DOI: 10.1073/pnas.1208775109
|View full text |Cite
|
Sign up to set email alerts
|

Molecular target validation, antimicrobial delivery, and potential treatment of Toxoplasma gondii infections

Abstract: Toxoplasma gondii persistently infects over two billion people worldwide. It can cause substantial morbidity and mortality. Existing treatments have associated toxicities and hypersensitivity and do not eliminate encysted bradyzoites that recrudesce. New, improved medicines are needed. Transductive peptides carry small molecule cargos across multiple membranes to enter intracellular tachyzoites and encysted bradyzoites. They also carry cargos into retina when applied topically to eyes, and cross blood brain ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 9 publications
(12 reference statements)
2
33
0
Order By: Relevance
“…PPMOs are produced following conjugation of a specific MO to a cell-penetrating, arginine-rich peptide, whereas VMOs are synthesized as conjugates between a MO molecule and an octa-guanidinium head group (13,17,24). To date, VMOs have been used to downregulate gene expression in human fibroblasts, mice, zebrafish, Xenopus oocytes, Toxoplasma gondii, and other model organisms (20,(25)(26)(27)(28)(29). However, these conjugates have not yet been assessed for their use in functional analysis of P. falciparum genes.…”
mentioning
confidence: 99%
“…PPMOs are produced following conjugation of a specific MO to a cell-penetrating, arginine-rich peptide, whereas VMOs are synthesized as conjugates between a MO molecule and an octa-guanidinium head group (13,17,24). To date, VMOs have been used to downregulate gene expression in human fibroblasts, mice, zebrafish, Xenopus oocytes, Toxoplasma gondii, and other model organisms (20,(25)(26)(27)(28)(29). However, these conjugates have not yet been assessed for their use in functional analysis of P. falciparum genes.…”
mentioning
confidence: 99%
“…The parasite endures throughout a person's life and although research for a cure is ongoing, there is currently no treatment, which can eliminate it from the human system, nor an available vaccine. Dr Rima McLeod and her team of researchers at the University of Chicago, however, have been seeking to develop a successful approach using strands of DNA with a small peptide, inserted into cells which contain the parasite, in an attempt to disrupt genetic signals (Lai et al, 2012). The new treatment was tested in tissue culture containing infected cells and in live mice, artifi cially infected with the parasite.…”
Section: Treatment For Toxoplasmosismentioning
confidence: 99%
“…(5) The knockdown of T. gondii ATPase4 (TgATP4) with exon skipping or a translation-inhibiting peptide-conjugated phosphorodiamidate morpholino oligomer (PPMO; a molecular transporter-conjugated antisense morpholino) (7) but not offtarget PPMO (7) showed that TgATP4 was also essential for replication (Fig. 1F).…”
mentioning
confidence: 99%
“…Once the most effective spiroindolone is identified, the mode of solubilization and administration can be optimized. A variety of models are available for such future studies (1,4,7,12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation